The young learner's handbook - Tchudi, Stephen, 1942- (New York : Scribner, 1987)
Explores the areas of expanding knowledge, gathering data, applying information, and developing a curious mind.
Includes index.
Bibliography: p. 179-181.
6.9
7-10.
Keywords: Learning -- Juvenile literature; Problem solving in children -- Juvenile literature; Research -- Juvenile literature; Thought and thinking -- Juvenile literature; Learning -- Psychology; Problem solving; Research; Thought and thinking; Problem solving; Psychology of learning; Research; Thought and thinking